Frequency of dementia among elderly admitted to a Geriatrics Inpatients Sector of a Brazilian public hospital - Rafael Thomazi; Liciana Vaz de Arruda Silveira; Paulo José Fortes Villas Boas; Alessandro Ferrari Jacinto (Dementia & Neuropsychologia)
ABSTRACT Patients with dementia are commonly admitted to inpatient sectors. The aim of this study was to describe the frequency of dementia among elderly inpatients admitted to the Geriatrics Sector of a Brazilian Tertiary University Hospital, and to identify associations between dementia and clinical and sociodemographic factors. Methods: All patients admitted to the Geriatrics Sector of a public Brazilian university-hospital from March 1st 2014 to January 31st 2015 were assessed by geriatricians. The patients were divided into groups "with or without diagnosis of dementia". Univariate analysis was performed between these two groups using the Chi-Square Test, Student's t-test or the Mann-Whitney Test. Results: One hundred and three elderly inpatients, with a mean age of 82 (±7.9) years, were assessed. Overall, 74.7% had low educational level (<4 years), 66% used polypharmacy, 57.2% developed delirium during hospitalization and 59% were totally dependent for basic activities of daily living. The diagnosis of dementia was observed in 59 (57%) subjects. Conclusion: The frequency of dementia was high among the elderly inpatients evaluated. The association between dementia and certain clinical conditions, such as incontinence, delirium and use of psychoactive drugs, was in line with the medical literature.